The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3109/10253890.2015.1078305
|View full text |Cite
|
Sign up to set email alerts
|

Restraint stress delays endometrial adaptive remodeling during mouse embryo implantation

Abstract: We showed previously in mice that restraint stress reduces the number of embryo implantation sites in the endometrium. Here we hypothesized that the uterine microenvironment is altered by restraint stress and consequently is sub-optimal for embryo implantation. On embryonic day 1 (E1), 60 of 154 pregnant CD1 mice underwent restraint stress (4h), repeated daily to E3, E5 or E7 (n = 10 mice per group). Restraint stress decreased food intake and suppressed body weight gain on E3, E5 and E7. Restraint stress decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
(38 reference statements)
3
14
0
3
Order By: Relevance
“…Therefore, the uterus may be an important organ for studying reproductive stress exposure as a form of psychological stress. Additionally, in the present study, we found that restraint stress affected the balance between oxidation and antioxidation [10], as well as the balance between proliferation and apoptosis, under restraint stress in early pregnancy [21]. Recently, psychological stress has attracted worldwide attention.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Therefore, the uterus may be an important organ for studying reproductive stress exposure as a form of psychological stress. Additionally, in the present study, we found that restraint stress affected the balance between oxidation and antioxidation [10], as well as the balance between proliferation and apoptosis, under restraint stress in early pregnancy [21]. Recently, psychological stress has attracted worldwide attention.…”
Section: Discussionsupporting
confidence: 58%
“…Primary mouse uterine stromal cells from E5 pregnant mouse uteri were isolated as described in a related study [21]. Briefly, uterine tissue from E5 mice was removed from the fat tissue, cut longitudinally, and washed with Hanks' balanced salt solution (HBSS, containing 100 U/mL penicillin and 100 µg/mL streptomycin).…”
Section: Primary Culture Of Uterine Stromal Cells and Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, restraint stress markedly decreased the CD3 + CD4 + T/CD3 + CD8 + T cell ratio. Additionally, antioxidant ability was compromised, and the concentration of MDA was increased [ 86 ]. Moreover, restraint stress reduced the weight of the uterus and ovary and the intake of food with reduction in weight, while the relative endometrial area and uterine gland area were reduced after restraint stress.…”
Section: Oxidative Stress In the Uterus And Placentamentioning
confidence: 99%
“…Restraint stress in pregnant mice significantly reduced the pregnancy rate and average litter size of mice as compared to controls, attributed in part to reduced number of implantation sites [ 46 ]. Decreased endometrial cell proliferation, vascular endothelial growth factor expression, and microvessel density were found in mated female mice exposed to restraint stress, which may provide some insight into the mechanisms by which restraint stress negatively influences the uterine environment [ 47 ]. Auditory stress on female mice has also been reported to have adverse effects on uterine receptivity [ 48 ].…”
Section: The Impacts Of Stress Throughout the Hpg Axismentioning
confidence: 99%